2018
DOI: 10.1038/s41467-018-05827-9
|View full text |Cite
|
Sign up to set email alerts
|

V2a interneuron diversity tailors spinal circuit organization to control the vigor of locomotor movements

Abstract: Locomotion is a complex motor task generated by spinal circuits driving motoneurons in a precise sequence to control the timing and vigor of movements, but the underlying circuit logic remains to be understood. Here we reveal, in adult zebrafish, how the diversity and selective distribution of two V2a interneuron types within the locomotor network transform commands into an appropriate, task-dependent circuit organization. Bursting-type V2a interneurons with unidirectional axons predominantly target distal den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 79 publications
8
75
0
Order By: Relevance
“…Although substantial progress has been made in describing spinal cell types and projection patterns 2,4,32,42,43,44,45 remarkably little is known about connectivity in motor circuits. Indeed, the size and extent of the neuronal population involved in generating motor activity are unknown, and essential features of graph theory, such convergence versus divergence, degree distributions, 29 and sparseness remain open issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial progress has been made in describing spinal cell types and projection patterns 2,4,32,42,43,44,45 remarkably little is known about connectivity in motor circuits. Indeed, the size and extent of the neuronal population involved in generating motor activity are unknown, and essential features of graph theory, such convergence versus divergence, degree distributions, 29 and sparseness remain open issues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the anatomical and functional organization of the V2a interneurons neglected the possibility that they might co-express and potentially co-release neurotransmitters other than glutamate (Ampatzis et al, 2014;Ausborn et al, 2012;Dougherty and Kiehn, 2010). However, earlier studies on zebrafish (Ampatzis et al, 2014;Ausborn et al, 2012;Song et al, 2018) and mice (Al-Mosawie et al, 2007;Zhong et al, 2011) clearly demonstrated that the V2a interneurons are functionally heterogeneous. In particular, the V2a interneurons in adult zebrafish form three discrete functional subpopulations that are incrementally recruited at different speeds of locomotion, and their recruitment pattern is not topographically organized (Ampatzis et al, 2014;Ausborn et al, 2012;Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate our findings and the extent of neurotransmitter co-expression and dynamics, we performed a proof-of-concept analysis focusing on one of the most well-characterized spinal interneuron populations, the V2a interneurons (Arber, 2012;Goulding, 2009;Kiehn, 2016;2011). V2a interneurons are one of the most important excitatory neuronal classes for the operation of the vertebrate locomotor network (Al-Mosawie et al, 2007;Crone et al, 2008;Dougherty and Kiehn, 2010;Hayashi et al, 2018;Joshi et al, 2009;Lundfald et al, 2007;Zhong et al, 2011), as demonstrated by studies on zebrafish (Ampatzis et al, 2014;Ausborn et al, 2012;Eklöf-Ljunggren et al, 2012;Kimura et al, 2006;McLean et al, 2008;McLean and Fetcho 2009;Menelaou et al, 2014;Song et al, 2018). In keeping with previous reports (Ampatzis et al, 2014), we detected 23.59 ± 0.503 V2a interneurons (n = 22 zebrafish; Figure S4B) per hemisegment in the adult zebrafish spinal cord.…”
Section: V2a Interneuron Neurotransmitter Diversity: a Proof-of-concementioning
confidence: 99%
“…Although BPNs are necessary for fast walking, the ability of BPNs to drive different walking speeds at different stimulation frequencies, provides an opportunity to examine downstream mechanisms for speed control. Recent studies in zebrafish (Ampatzis et al, 2014;Song et al, 2018) show a gradient of recruitment of distinct premotor circuits at increasing swimming speeds. In Drosophila, recent work (Azevedo et al 2019) has characterized distinct motor neurons recruited in a similar manner as leg movements accelerate.…”
Section: Bolt Protocerebral Neurons (Bpns) Drive Fast Straight Forwamentioning
confidence: 99%